2016
DOI: 10.1111/jir.12343
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the AIR Self‐Determination Scale: the Chinese version (AIR SDS‐C) for Chinese people with intellectual disabilities

Abstract: The AIR SDS-C appears to be a valid and reliable scale. This study examined adult groups as well as student groups. The application of the scale can thus be extended to a wider population. The implications for theory building and practice are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…However, according to the literature, the student form of the AIR-Scale had previously been adapted to Turkish and the sub-dimensions had yielded results that were consistent with the original form (Arslan & Özmete, 2015). Similarly, it was found that the Spanish (Mumbardó, Guàrdia Olmos, & Giné, 2018), Norwegian (Garrels, & Granlund, 2018), and Chinese (Wong, et al, 2017) versions of the scale had also yielded results that were consistent with the original scale.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, according to the literature, the student form of the AIR-Scale had previously been adapted to Turkish and the sub-dimensions had yielded results that were consistent with the original form (Arslan & Özmete, 2015). Similarly, it was found that the Spanish (Mumbardó, Guàrdia Olmos, & Giné, 2018), Norwegian (Garrels, & Granlund, 2018), and Chinese (Wong, et al, 2017) versions of the scale had also yielded results that were consistent with the original scale.…”
Section: Discussionmentioning
confidence: 85%
“…Although various measurement tools have been developed to measure self-determination skills in the field of intellectual disabilities, only the Arc's Self-Determination Scale, developed by Wehmeyer & Kelchner (1995), and the AIR, (Wolman et al, 1994), which is the measurement tool of American Research Institute, were designed to measure self-determination globally. The AIR Self-Determination Scale had previously been translated into Spanish (Mumbardó, Guàrdia Olmos, & Giné, 2018), Norwegian (Garrels, & Granlund, 2018), and Chinese (Wong, et al, 2017). However, there is not enough research on the appropriateness and application of self-determination skills to students with different linguistic and cultural backgrounds.…”
Section: Cultural Differencesmentioning
confidence: 99%
“…Results of the CFA suggested a relatively good fit of the data to the model (χ 2 (df = 246, n = 356) = 391.64, χ 2 /df = 1.59, RMSEA = 0.041 90% CI [0.033-0.048], CFI = 0.933, TLI = 0.925, SRMR = 0.05). The AIR SDS-C also showed good levels of internal reliability (α = 0.88) [35].…”
Section: The Self-determination Competencies Section Of the Air Self-determination Scale-chinese Version (Air Sds-c)mentioning
confidence: 88%
“…The first section was an open-ended item that collected the participants' personal goals. The second section measured the participants' self-determination competencies (the independent variable) by using the first section of the AIR Self-Determination Scale-Chinese Version (AIR SDS-C) [35]. The third section measured personal well-being (the dependent variable) by using the Personal Well-Being-Intellectual Disability (Cantonese) 3rd Edition (PWI-C) [36].…”
Section: Methodsmentioning
confidence: 99%
“…CFA can support further evidence regarding the fitness of the proposed model with regard to the structure of the factors identified via EFA. The CFA is presented in route diagrams where the circles represent latent variables and the squares represent observed variables (Wong, Wong and Zhuang & Liu, 2017). The single-headed arrows are used to imply an assumed direction of influence, and the twoheaded arrows represent the covariance between the six latent variables (Figure 1).…”
Section: Exploratory Factor Analysismentioning
confidence: 99%